Identifying distribution and accumulation patterns of floating marine debris in the Black Sea. (April 2020) - Miladinova, S.; Macias, D.; Stips, A.; Garcia-Gorriz, E.
Abstract: The distribution and accumulation of floating marine debris in the Black Sea during the last few decades are analysed by the help of numerical modelling. An approach based on a mesoscale circulation model combined with a particle tracking model is applied. It is established that the litter distribution is nearly independent of the source location and is mainly controlled by the basin circulation system. The western gyre predominantly accumulates floating debris in summer. After the integration of the main cyclonic current in winter, the debris in the inner basin moves east. Retention zones along the south-western coast persist in time. The mean particle stranding time is estimated at about 200 days. Accumulation zones along the south-eastern and eastern coast are abundant in summer, and then move further northeast and north. Simulations demonstrate an increasing litter accumulation in summer on the North Western Shelf and shelf break. Graphical abstract: Unlabelled Image Highlights: Floating litter is explored by eddy resolving and particle tracking models. The litter distribution is nearly independent of the source location. The western gyre accumulates floating debris in summer. Retention zones along the south-western coast persist in time. South-eastern accumulation zones move northeast and north in winter.